METAFORA KONSEPTUAL “POLITIK ADALAH PERANG” DALAM PIDATO KENEGARAAN PRABOWO SUBIANTO - Eva Maria; Merry Lapasau; Kristyan Dwi Aryanto; Rina Maryana; Supendi; Yanti Nuraida (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
Using conceptual metaphors in political speeches can arguably be powerful because speakers need to deliver both the message and the ideological effect to attract the audience’s attention. The study aims to examine the use of metaphors in the first political speech delivered by President Prabowo Subianto during the Plenary Session of the People’s Consultative Assembly of the Republic of Indonesia on October 20, 2024. This qualitative study draws on Critical Discourse Analysis and Conceptual Metaphor Theory. The speech video and its transcript posted on the KOMPAS.TV YouTube channel were chosen as data sources. Four domains of metaphor and four cases of target domain conceptualization were found. These metaphors were conceptualized using several source domains, the most frequent of which is war and physical struggle applied to domestic issues. The findings also suggest that the military characteristics strongly attached to Prabowo Subianto did not produce an aggressive or confrontational rhetorical style. Instead, the source domain of